Design and fabrication of simple geometric patterns - Lua, Ying Han. (2013)
Most of the pattern designs found in latticework consist of motifs that are arranged in a rhythmic manner. This project aims to design simple motifs and create patterns designs using created motifs. These patterns can be applied to structures like windows and doors. This is achieved by using a Computer Aided Design (CAD) software equipped with an Application Program Interface (API) program.